Value and virtue in a godless universe - Wielenberg, Erik J. (Erik Joseph), 1972- (Cambridge University Press, 2005)
In this book, Erik J. Wielenberg disputes the belief that without God there are no moral obligations and that notions of virtue and vice and good and evil have no place. Wielenberg argues that these terms do retain meaning and ethical import even if God does not exist.